(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Indecision corrupts several characters in Hamlet by William Shakespeare. Hamlet must revenge the death of his father, but he will postpone the act. The most important thing. While Hamlet is the source of all evil in the play, he is more opposed to the evil than other people. Hamlet is dying of delaying the king’s killing. This indecisive act leads to a brutal end, full of death misery. Indecision affects not only the undecided person, but those who are around. Decisions which have not been taken will result in disaster death, as in the case of Hamlet and even in the world of today. It is important that decisions are taken immediately and without hesitation in times of crisis. After the play comes Hamlet’s second moment of indecision. Hamlet needs more proof that Claudius is responsible for the murder of his father. The players are then asked to make a certain decision.